PENYIMPANGAN SOSIAL (SIKAP MASYARAKAT TERHADAP PEREMPUAN HAMIL DI LUAR NIKAH) DI DESA TPI KECAMATAN TOBELO KABUPATEN HALMAHERA UTARA PROVINSI MALUKU UTARA - Afri Rifyanti Mandak; Ferdinand Kerebungu; Hamdi Gugule (Labor Program Studi Pendidikan Sosiologi, 2020)
The problem in this research is about the society's attitude towards women who get pregnant outside of marriage in TPI village. Women who are pregnant without a husband will usually bear the shame and will be isolated in the community. For this reason, parents and even the surrounding community, if it is related to pregnancy outside of marriage, they strongly disagree because they think this will set a bad example for others. By using qualitative research methods and observation and interview data collection techniques, the following research results are obtained, namely the attitude of the community towards social deviations that occur in the TPI village, Tobelo District, North Halmahera Regency. Pregnancy outside of marriage is considered taboo, even seen as a disgrace in society. Pregnancy outside of marriage means deviant behavior because in it there are elements that violate the norms or teachings that exist in a community group.